Critérios de irracionalidade e o teorema de Apéry - Monte, Luiz Antônio Caetano (2007)
This dissertation show several criterion of irrationality As an application of these criteria prove that some false theta functions of Ramanujan of Watson and q-series of Rogers-Ramanujan of take irrational values in -1/q is 1/q where q is integer most or equal an 2. To end prove the irrationality of zeta three